2006
DOI: 10.1074/jbc.m509065200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Lipid Peroxidation Product as a Potential Trigger of the p53 Pathway

Abstract: The tumor suppressor and transcription factor p53 is a key modulator of cellular stress responses, and activation of p53 can trigger apoptosis in many cell types, including neurons. We found that this nuclear protein was significantly phosphorylated when human neuroblastoma SH-SY5Y cells were exposed to in vitro oxidized polyunsaturated fatty acids. To identify an oxidized lipid that induces p53 phosphorylation, we conducted a screening of lipid peroxidation products in human neuroblastoma SH-SY5Y cells and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 48 publications
(48 reference statements)
2
50
0
Order By: Relevance
“…Perfluorooctane sulfonate does not appear to be genotoxic [50][51][52], although Liu et al [34] did report DNA damage at high PFOS exposures but concluded that it was likely apoptosis related. Recent evidence has shown that lipid peroxidation products can activate TP53 [53], which may explain results from the present study. The fact that both Mdm2, a gene that inactivates TP53, and Cdkn2A, which modulates Mdm2 activity [54], were both overexpressed following PFOS exposure is further evidence that TP53 activity was perturbed.…”
Section: Interaction Network and Potential Regulatory Moleculesmentioning
confidence: 47%
“…Perfluorooctane sulfonate does not appear to be genotoxic [50][51][52], although Liu et al [34] did report DNA damage at high PFOS exposures but concluded that it was likely apoptosis related. Recent evidence has shown that lipid peroxidation products can activate TP53 [53], which may explain results from the present study. The fact that both Mdm2, a gene that inactivates TP53, and Cdkn2A, which modulates Mdm2 activity [54], were both overexpressed following PFOS exposure is further evidence that TP53 activity was perturbed.…”
Section: Interaction Network and Potential Regulatory Moleculesmentioning
confidence: 47%
“…In addition to causing membrane instability and increasing the vulnerability of the cell to subsequent insults [28], lipid peroxidation can also generate harmful and relatively stable aldehyde products which add to the oxidative stress. One of these damaging aldehydes is 4-oxo-2-nonenal (ONE), which acts by activation of the p53 signaling pathway and induces apoptosis in SH-SY5Y neuroblastoma cells [42]. …”
Section: Discussionmentioning
confidence: 99%
“…This protein has been observed in unstable atherosclerotic carotid plaque and the p53 pathway may be activated by lipid peroxidation products, as observed in human neuroblastoma cells (4). Furthermore, the involvement of p53 in some age-associated morbidities such as diabetes (5) and fatty liver diseases (6) has also been described.…”
Section: Introductionmentioning
confidence: 96%